2020
DOI: 10.3390/met11010068
|View full text |Cite
|
Sign up to set email alerts
|

Heat Input and Mechanical Properties Investigation of Friction Stir Welded AA5083/AA5754 and AA5083/AA7020

Abstract: The current work presents a detailed investigation for the effect of a wide range friction stir welding (FSW) parameters on the dissimilar joints’ quality of aluminum alloys. Two groups of dissimilar weldments have been produced between AA5083/AA5754 and A5083/AA7020 using tool rotational rates range from 300 to 600 rpm, and tool traverse speeds range from 20 to 80 mm/min. In addition, the effect of reversing the position of the high strength alloy at the advancing side and at retreating side has been investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
(56 reference statements)
2
37
0
Order By: Relevance
“…As different welding parameters affect the mechanical properties of welded specimens, the feed rate, tool rotation speed, and tilting angle parameters must be evaluated together [18,20,24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As different welding parameters affect the mechanical properties of welded specimens, the feed rate, tool rotation speed, and tilting angle parameters must be evaluated together [18,20,24].…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al [24] investigated the effect of welding parameters on the joined dissimilar aluminium alloys (AA5083/AA5754 and A5083/AA7020) with FSW. The results showed that sound joints were obtained at the low heat input FSW parameters while increasing the heat input resulted in tunnel defects.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, visual tests (VT) were performed in accordance with the EN ISO 17637:2017 standard [53]. The VT for the FSW joints revealed cracks, lack of penetration and overheating of the plates as well as a certain amount of material outflow [35][36][37]. This information was of particular importance as it made it possible to select appropriate welding parameters for producing joints.…”
Section: Examination Proceduresmentioning
confidence: 99%
“…As FSW is a solid-state welding process, defects such as porosity or cold cracking do not occur. The most common defects in aluminium alloys are voids, kissing bonds, flash defects (material flow), lack of penetration or cracks [34][35][36][37]. These defects are mainly caused by incorrect parameter selection.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding (FSW) is a solid-state welding process [43][44][45][46] that has been used at the laboratory scale for welding both low-softening-temperature materials (Al, Cu, Mg) [45][46][47][48] and high-softening-temperature materials (Ti, Ni, steel alloys) [49][50][51]. However, in terms of industrial applications, only low-softening-temperature materials find their way into a large number of applications, such as shipbuilding, railway, aerospace and automotive [44].…”
Section: Fsw Tool For High-softening-temperature Materialsmentioning
confidence: 99%